Competitiveness of Indonesian edible bird’s nest in global markets (2017-2021) - HALKAM, HAMKA; DEMMALLINO, EYMAL BAHSAR; ALI, M. SALEH S.; SUHAB, SULTAN (Smujo International, 2026)
Abstract. Halkam H, Demmallino EB, Ali MSS, Suhab S. 2026. Competitiveness of Indonesian edible bird’s nest in global markets (2017-2021). Asian J Agric 10: g100106. https://doi.org/10.13057/asianjagric/g100106. Indonesia is the world’s largest producer and exporter of edible bird’s nest derived from Aerodramus fuciphagus. All edible bird’s nest produced in Indonesia is intended for export. During the period 2017 to 2021, Indonesia recorded an average annual export volume of 1,331 tons, with a total export value of US398.4 million. Despite this strong performance, Indonesia faces several challenges in international trade, including stringent requirements for direct exports to China and increasing competition from other exporting countries. This study aimed to assess Indonesia’s competitiveness in the global edible bird’s nest market. A quantitative, descriptive, and analytical approach was employed using secondary data. The results indicate that Indonesian edible bird’s nest exhibits strong competitiveness and rapid growth in global markets. This is reflected by a high revealed comparative advantage value of 85.24, which is substantially higher than that of competing exporting countries, a revealed symmetric comparative advantage value close to +1, a position as a rising star in the export product dynamic matrix, and classification as an optimistic product under the X-Model potential export product framework. The findings further suggest that national competitiveness in the global edible bird’s nest trade increases with higher export values. Price disparities across export destinations are primarily driven by destination-specific regulatory requirements. China imports edible bird’s nest at relatively high prices under strict regulatory standards, whereas Hong Kong applies fewer regulatory controls and offers lower purchase prices. As a result, increased export volumes to China generate a substantial rise in export value, while exports to Hong Kong do not yield a comparable effect. The study also reports a 358% increase in the swiftlet population in 2021 compared to 1993. To further enhance exports, particularly to China, the Indonesian government should strengthen the registration of swiftlet houses, expand edible bird’s nest cleaning facilities in producing regions, and support the development of value-added edible bird’s nest products.